Interleukin-22 From Type 3 Innate Lymphoid Cells Aggravates Lupus Nephritis by Promoting Macrophage Infiltration in Lupus-Prone Mice - Hu, Lingzhen; Hu, Jingyi; Chen, Liheng; Zhang, Yi; Wang, Qingqing; Yang, Xuyan (Frontiers in Immunology, 2021)
Lupus nephritis (LN) is one of the most severe manifestations of systemic lupus erythematosus (SLE). Our previous studies demonstrated increased serum and renal Interleukin (IL)-22 in LN patients and MRL/lpr mice. In tThis study, we aim to investigated the role of IL-22 and its mechanism in LN. Here, we found that IL-22 was mainly produced by type 3 innate lymphoid cells (ILC3) in kidney of MRL/lpr mice. The systemic illness and local renal lesion were significantly alleviated in IL-22 or IL-22R gene knockout (KO) mice (IL-22 KO or IL-22R KO MRL/lpr mice) than wild-type (WT control) mice (MRL/lpr mice). IL-22 KO or IL-22R KO MRL/lpr mice had significantly slighter infiltration of macrophage in kidney than MRL/lpr mice. Consistently, by RNA-Seq, the expression of (CC motif) ligand 2 (CCL2) and (CXC motif) ligand 10 (CXCL10) was decreased in kidney of KO mice compared with WT control mice. By immunoblotting, significantly increased levels of STAT3 phosphorylation were found in the kidney of WT control mice compared to KO mice. In vitro, primary kidney epithelial cells from WT control mouse stimulated with with recombinant IL-22 (rIL-22) expressed higher levels of CCL2, CXCL10 and phosphorylated STAT3. At the same time, when primary kidney epithelial cells were treated with rIL-22, transwell assay demonstrated their supernatant recruited more macrophages. In human kidney epithelial cell line (HK2) cells, when treated with rIL-22, we observed similar results with primary mouse kidney epithelial cells. Moreover, when cells were stimulated with rIL-22 following pre-treatment with STAT3 pathway inhibitor, the expression of CCL2 and CXCL10 were significantly reversed. Our findings demonstrate that IL-22 binding to IL-22R in kidney epithelial cells activated the STAT3 signaling pathway, enhanced the chemokine secretion and then promoted the infiltration macrophage in infiltration to the kidney of MRL/lpr mice, thus aggravated LN in lupus-prone mice. These findings indicate that IL-22 may play a pathogenic role in LN and be may provide a promising novel therapeutic target for LN.